Mode of delivery and outcome of breech presentation: a prospective observational study in a tertiary centre - Karning, Rashmi Kumar; B. T., Bhanu; Sarojini, . (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Breech presentation is the commonest malpresentation with the incidence of 3-4% at term. This study was done with the objective of studying the mode of delivery in breech presentation and to compare the maternal and fetal outcome in patients delivered vaginally to those delivered by cesarean section. Methods: This prospective observational study was conducted in Vanivilas Hospital, affiliated to Bangalore Medical College and Research Institute, from June 2014 to May 2015. The study group included 509 patients with breech presentation who were studied with respect to their gestational age, birth weight, type of breech, mode of delivery, maternal and perinatal outcome. Results: The incidence of breech presentation was 2.92% (509) among 17454 total deliveries with the incidence of 3.17% in primi and 2.73% in multies. 193 (38%) patients had vaginal breech delivery and 316 (62%) delivered by LSCS. Apgar score of less than 7 at 1 minute was seen with 21.42% of vaginally delivered fetuses and 9.09% of fetuses delivered by cesarean section. The perinatal mortality was 1.6% (8 cases) in vaginal group 0.8% (4 cases) in LSCS group. The short term maternal complications in LSCS group was 7.62% and in vaginal delivery group was 3.09%. Conclusions: The short term maternal morbidity is higher in patients with cesarean section compared to those with vaginal breech delivery. Perinatal outcome is better in babies delivered by cesarean section. Still vaginal breech delivery can be an option for breech babies with proper selection and when conducted by a skilled obstetrician.